SEJARAH PERKEMBANGAN YAYASAN SUARA HATI SIDOARJO TAHUN 2010-2018 - Muslichah Dwi Lestari (Program Studi Sejarah Peradaban Islam Fakultas Adab dan Humaniora UIN Sunan Ampel Surabaya, 2018)
Abstract: The article examines the history of the Suara Hati foundation from Sidoarjo. The problems examined in this thesis are: (1) What is the history of the founding of the Suara Hati Sidoarjo Foundation (2) How did the development of the Sidoarjo Suara Hati Foundation in 2010–2018 (3) What are the supporting and inhibiting factors of the Sidoarjo Suara Hati Foundation. The author uses the historical method through heuristic, verification, interpretation, and historiographical stages. In this study, the authors use a historical approach and a social approach. Meanwhile, the theory uses two theories, namely: First, the challenge and response by Arnold J. Toynbee. Second, the theory of continuity and change by John Obert Voll (From the results of the research that has been done, it can be concluded that (1) the Suara Hati Sidoarjo Foundation was officially established on February 8, 2010. The Suara Hati Sidoarjo Foundation is a foundation engaged in three services the main social fields, namely social health, education, and social welfare (2) The Suara Hati Sidoarjo Foundation has experienced developments from various aspects since 2010-2018 which include the development of infrastructure, activities, and funding systems. The activities of the foundation have experienced developments in terms of entrepreneurship and religion The funding system relies on donors and businesses started by foundations (3) The supporting factors for the development of the Suara Hati Sidoarjo Foundation include the community, funding sources, human resources, publications and infrastructure, while the inhibiting factors are legality registration, the environment, combining idealism , financial resources in the early standing only the foundation, the lack of infrastructure and constraints on the recruitment of volunteers. Keywords: Suara Hati, development, support, resistor